Deteksi Dini Perilaku Koruptif Pengguna Pojok Baca KPK di Perpustakaan Kabupaten Klaten - Muhammad Zulfikar; Sumaryati Sumaryati; Sri Mulyati (Universitas Muhammadiyah Ponorogo, 2026)
Early Detection of Corrupt Behavior Among Users of the KPK Reading Corner at the Klaten Regency Library. This study aims to conduct early detection of corrupt behavioral tendencies among users of the KPK Reading Corner at Klaten Regency Library. Corrupt behavior represents a deviant social action that poses serious challenges to Indonesia, with the Corrupt Behavior Index increasing by 1.8% in 2024. The research employs a descriptive quantitative approach involving 36 respondents selected through purposive sampling based on active user criteria of the KPK Reading Corner. The research instrument consists of an online-based questionnaire using a 0– 2 Likert scale measuring seven indicators of corrupt behavior, including honesty, integrity, gratification, responsibility, legal discipline, social awareness, and anti-corruption spirit. Research findings indicate that 19.4% of respondents fall into the low-risk category, 52.8% into the medium-risk category, and 27.8% into the high-risk category. Although the majority of respondents demonstrate adequate initial awareness of anti-corruption values, a significant finding reveals that a portion of respondents admitted to